Compliance to HIV treatment monitoring guidelines can reduce laboratory costs - Naseem Cassim; Lindi M. Coetzee; Kathryn Schnippel; Deborah K. Glencross (AOSIS, 2016)
Background: Panel tests are a predetermined group of tests commonly requested together to provide a comprehensive and conclusive diagnosis, for example, liver function test (LFT). South African HIV antiretroviral treatment (ART) guidelines recommend individual tests for toxicity monitoring over panel tests. In 2008, the National Health Laboratory Services (NHLS) request form was redesigned to list individual tests instead of panel tests and removed the 'other tests' box option to facilitate efficient ART laboratory monitoring. Objectives: This study aimed to demonstrate changes in laboratory expenditure, for individual and panel tests, for ART toxicity monitoring. Method: NHLS Corporate Data Warehouse (CDW) data were extracted for HIV conditional grant accounts to assess ART toxicity monitoring laboratory expenditure between 2010/2011 and 2014/2015. Data were classified based on the tests requested, as either panel (LFT or urea and electrolytes) or individual (alanine transaminase or creatinine) tests. Results: Expenditure on panel tests reduced from R340 million in 2010/2011 to R140m by 2014/2015 (reduction of R204m) and individual test expenditure increased from R34m to R76m (twofold increase). A significant reduction in LFT panel expenditure was noted, reducing from R322m in 2010/2011 to R130m in 2014/2015 (60% reduction). Conclusion: Changes in toxicity monitoring guidelines and the re-engineering of the NHLS request form successfully reduced expenditure on panel tests relative to individual tests. The introduction of order entry systems could further reduce unnecessary laboratory expenditure. Keywords: HIV;ART;Toxicity Monitoring;Expenditure